Development Of Gis Based Mapping System For Future Main Campus Infrastructure Managing Spatial Information - Shahrom, Mohamad Shamsul Nizam (Universiti Sains Malaysia, 2005)
The integration between ArcView GIS with AutoCAD and Idrisi32 is for designing and developing a database for Universiti Sains Malaysia information centre in the future. This project also practices a data analysis through the integration of satellite image and engineering drawing as known as ‘As Built Map’. All the information and analysis are combined and assumed to be the basic tool for managing the campus development that is called Universiti Sains Malaysia Map Explorer or USM – Me. The project process begins with collecting data from School of Civil Engineering like satellite image and AutoCAD drawing of USM main campus. The satellite image was customized with Idrisi32 while the drawing edit in AutoCAD. The two data were brought into ArcView GIS using specialized command and tool. The drawing in DWG format was changed to ArcView GIS format while the raster image in Idrisi32 was changed into TIFF image format. These two data were changed in ArcView GIS and combined with the other data. Generally, one database designed for people demand and situation with all data that has collected in one system tool been created.